MONITORAMENTO DO LENÇOL FREÁTICO RASO NO DISTRITO DE SÃO FRANCISCO-MERUOCA/CE - Vasconcelos, Mickaelon Belchior; Silva, Carla Maria Salgado Vidal; Santiago, Marlúcia Freitas; Vasconcelos, Andreazza Belchior (Águas Subterrâneas, 2001)
Resumo não disponível.